2021
DOI: 10.1159/000518943
|View full text |Cite
|
Sign up to set email alerts
|

Surface Free Energy, Interaction, and Adsorption of Calcium and Phosphate to Enamel Treated with Trimetaphosphate and Glycerophosphate

Abstract: This study aimed to evaluate the surface (γ s ) and interaction (ΔG iwi ) free energy and calcium (Ca 2+ ) and phosphate (PO 4 3− ) adsorption to dental enamel treated with sodium trimetaphosphate (TMP) or calcium glycerophosphate (CaGP) that had or had not been exposed to CaPO 4 -containing solutions. Bovine enamel blocks (n = 192; 24 blocks/group) were treated (2 mL/block; 2 min) with TMP (0%, 1%, 3%, and 9%) and CaGP (0, 0.25, 0.5, and 1%) or exposed to a CaPO 4 -containing solution. The adsorption of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…In stage II of the experiment (the next day), participants used a toothpaste with calcium glycerophosphate to clean their teeth [ 36 , 37 ]. Thirty minutes after oral hygiene and rinsing with clean water, biofilm was collected from the two groups of study participants for a second time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In stage II of the experiment (the next day), participants used a toothpaste with calcium glycerophosphate to clean their teeth [ 36 , 37 ]. Thirty minutes after oral hygiene and rinsing with clean water, biofilm was collected from the two groups of study participants for a second time.…”
Section: Methodsmentioning
confidence: 99%
“…The next day, after a meal, participants began taking tablets containing a mineral complex with calcium glycerophosphate [ 36 , 37 ]. Participants took one tablet, three times per day.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, sodium trimetaphosphate (STMP, Na 3 P 3 O 9 ) is a cyclic polyphosphate working as an effective crosslinker, not showing toxicity at any concentration, and has been used in the food industry since being FDA-approved for humans [20]. Studies investigating the potential of STMP found that it provides nucleation sites for calcium phosphate apatite precipitation [21] since it leads to a more anionic surface [22,23]. When added to a polyamide-based scaffold, STMP produced higher elastic modulus, elongation at break, and tensile strength, in addition to generating a hydrophilic surface that facilitates cell adhesion, which is essential for bone repair [24].…”
Section: Of 18mentioning
confidence: 99%
“…In the first (I) stage, the biofilm was taken on the first day of the experiment. The next day, the patients began to take tablets containing a mineral complex with calcium glycerophosphate [60,61]. According to the recommendations of the producer, the participants took one tablet 3 times a day.…”
Section: Design Of the Studymentioning
confidence: 99%